Perancangan Meja Kerja Penempatan Rapat dengan Metode Optimasi Utilitas Luas Permukaan - Ilyas Mas'udin (Department Industrial Engineering, University of Muhammadiyah Malang, 2000)
Placing same different I various dimension (length and width ) problem on work station to process at a machine is a similar problem with